Mitochondria-driven elimination of cancer and senescent cells - Hubackova, Sona; Magalhaes Novais, Silvia; Davidova, Eliska; Neuzil, Jiri; Rohlena, Jakub (Biological chemistry, 2019)
Mitochondria and oxidative phosphorylation (OXPHOS) are emerging as intriguing targets for the efficient elimination of cancer cells. The specificity of this approach is aided by the capacity of non-proliferating non-cancerous cells to withstand oxidative insult induced by OXPHOS inhibition. Recently we discovered that mitochondrial targeting can also be employed to eliminate senescent cells, where it breaks the interplay between OXPHOS and ATP transporters that appear important for the maintenance of mitochondrial morphology and viability in the senescent setting. Hence, mitochondria/OXPHOS directed pharmacological interventions show promise in several clinically-relevant scenarios that call for selective removal of cancer and senescent cells.
Keywords: Mitochondria; reaktivní formy kyslíku; Oxidative Phosphorylation; adenosintrifosfát; Adenosine Diphosphate; Humans; oxidativní fosforylace; stárnutí buněk; adenosindifosfát; buněčná smrt; lidé; mitochondrie; proliferace buněk; Reactive Oxygen Species; Adenosine Triphosphate; biologický transport; Cell Proliferation; Neoplasms; nádory; Cellular Senescence; Cell Death; Biological Transport